Low cost housing delivery in the Northern Province with reference to the Central Region - Matlala, M. M (University of Limpopo, 2000)
Refer to the document
Thesis (MPA.) -- University of Limpopo, 2000.
Keywords: Low cost housing; Housing -- South Africa -- Limpopo; Housing policy -- South Africa -- Limpopo; Low-income housing -- South Africa -- Limpopo